Probing the explanation of the muon (g-2) anomaly and thermal light dark matter with the semi-visible dark photon channel; European Physical Journal C; Vol. 81, iss. 10 - Cazzaniga C .; Odagiu P.; Depero E. Emanuele; Donskov S. V. Sergey Vasiljevich; Chumakov A. G. Aleksandr Grigorjevich; Dusaev R. R. Renat Ramilyevich; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Trifonov A. Yu. Andrey Yurievich; Vasilishin B. I. Bogdan Ivanovich (2021, 2021)
Title screen